1997
DOI: 10.1128/jcm.35.7.1859-1861.1997
|View full text |Cite
|
Sign up to set email alerts
|

Simple, speedy, sensitive, and specific serodiagnosis of pertussis by using a particle agglutination test

Abstract: We developed a particle agglutination test (KPA) with poly(␥-methyl L-glutamate) as the solid particle for measurement of pertussis toxin (PT) antibody. In this study, KPA was assessed as a means of serodiagnosing pertussis, and the results were compared with those of indirect enzyme-linked immunosorbent assay (indirect ELISA) and the microagglutination test. First, four serum samples were collected from each of 21 healthy children: before and 4 weeks after receiving three primary doses of acellular pertussis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In their recent communication, Aoyama et al (1) reported that they were successful in obtaining a serological diagnosis of pertussis by using Bordetella pertussis toxin (PT)-sensitized porous, spherical, poly(␥-methyl-L-glutamate) particles. The particle agglutination test (KPA) was standardized for detection and quantification of immunoglobulin G (IgG) against PT by comparison of serological results with those obtained by indirect enzyme-linked immunosorbent assay and the microagglutination test.…”
mentioning
confidence: 99%
“…In their recent communication, Aoyama et al (1) reported that they were successful in obtaining a serological diagnosis of pertussis by using Bordetella pertussis toxin (PT)-sensitized porous, spherical, poly(␥-methyl-L-glutamate) particles. The particle agglutination test (KPA) was standardized for detection and quantification of immunoglobulin G (IgG) against PT by comparison of serological results with those obtained by indirect enzyme-linked immunosorbent assay and the microagglutination test.…”
mentioning
confidence: 99%